PHILOTHEOS KOKKINOS’S HYPOMNĒMA ON SAINT NIKODEMOS THE YOUNGER (BHG 2307) - MITREA, Mihail (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2019)
Philotheos Kokkinos was one of the most prolific late-Byzantine hagiographers, who eulogized saints of old, as well as contemporaneous holy figures. He dedicated the first among his vitae of contemporaneous saints to the little-known holy man Nikodemos the Younger from the Philokalles monastery in Thessalonike. While superior of this monastery, Kokkinos gathered information about the holy man’s life and arranged it into the form of a short vita, titled hypomnēma (BHG 2307). This article analyzes the ways in which Kokkinos constructed an identity in narrative form for Nikodemos, exploring elements of holy foolery, hesychast influences, the miracle accounts weaved into the narrative, as well as its intended audience.